From techno talk to social reflection (Ökologisches Wirtschaften - Fachzeitschrift, 2010)
In politics many things depend on how an issue is framed from different points of view, including science and technology, society and public engagement. This threefold-framing of converging technologies has shaped the political and public debate on the topic. What are the lessons for the role of public participation in the field of converging technologies?